Values-Based Supply Chains: Supporting Regional Food and Farms. (February 2014) - Hardesty, Shermain; Feenstra, Gail; Visher, David; Lerman, Tracy; Thilmany-McFadden, Dawn; Bauman, Allison; Gillpatrick, Tom; Rainbolt, Gretchen Nurse
Values-based supply chains (VBSCs) have emerged as a structure to enhance the viability of mid-scale farms while preserving jobs and rural economies. They involve partnerships between producers, processors, distributors, retailers, and food service operators who share environmental, economic, and/or social values. We developed case studies and interviewed key informants to analyze the impacts of access to capital, regulations, infrastructure, and business acumen on the success of VBSCs. Communicating the benefits of VBSCs' products to customers, as well as to the VBSC partners, was instrumental to the success of the VBSCs in our case studies. However, our key informants emphasized that additional communications are needed to develop markets for VBSCs' products. Scale-appropriate infrastructure is also required, but funders are not convinced that these investments are secure. Successful VBSCs operate with economies of scale to broaden demand for their products while also generating fair returns to producers and other supply chain partners.